USING PEER TUTORING TECHNIQUE TO IMPROVE THE STUDENTS READING COMPREHENSION (A Collaborative Classroom Action Research to the Second Grade Students of Sma N 1 Juli) - Misnar Misnar; Uswatun Hasanah (Jurnal Pendidikan Almuslim, 2017)
This article aims to improve the student’s ability in reading comprehension and to know the students’ response in implementing peer tutoring technique. The problem faced in this research were the students also kept silent during teaching learning process. They were passive and had no courage to share ideas with their friends and tended to work individually. They were not able to improve and to find the main idea of each paragraph. They had difficulties to differentiate between the main idea and supporting details. The problem also came from the teacher because did not use appropriate method in teaching reading. To solve this problem the researcher applied peer tutoring technique. The sample of this research were the second grade students of SMAN 1 Juli. Data analysis was qualitative research. After implementing peer tutoring technique the result of research was 75, it was categorized very good and reached the criteria of success. The students’ response was 4.1. It Means that the implementation of peer tutoring technique was success in teaching reading comprehension at SMAN 1 Juli. Keywords: Peer tutoring, Reading comprehension